Antidepressant Use After Aneurysmal Subarachnoid Hemorrhage: A Population-Based Case–Control Study. Issue 9 (September 2016) - Huttunen, Jukka; Lindgren, Antti; Kurki, Mitja I.; Huttunen, Terhi; Frösen, Juhana; von und zu Fraunberg, Mikael; Koivisto, Timo; Kälviäinen, Reetta; Räikkönen, Katri; Viinamäki, Heimo; Jääskeläinen, Juha E.; Immonen, Arto
Abstract : Background and Purpose—: To elucidate the predictors of antidepressant use after subarachnoid hemorrhage from saccular intracranial aneurysm (sIA-SAH) in a population-based cohort with matched controls. Methods—: The Kuopio sIA database includes all unruptured and ruptured sIA cases admitted to the Kuopio University Hospital from its defined catchment population in Eastern Finland, with 3 matched controls for each patient. The use of all prescribed medicines has been fused from the Finnish national registry of prescribed medicines. In the present study, 2 or more purchases of antidepressant medication indicated antidepressant use. The risk factors of the antidepressant use were analyzed in 940 patients alive 12 months after sIA-SAH, and the classification tree analysis was used to create a predicting model for antidepressant use after sIA-SAH. Results—: The 940 12-month survivors of sIA-SAH had significantly more antidepressant use (odds ratio, 2.6; 95% confidence interval, 2.2–3.1) than their 2676 matched controls (29% versus 14%). Classification tree analysis, based on independent risk factors, was used for the best prediction model of antidepressant use after sIA-SAH. Modified Rankin Scale until 12 months was the most potent predictor, followed by condition (Hunt and Hess Scale) and age on admission for sIA-SAH. Conclusions—: The sIA-SAH survivors use significantly more often antidepressants, indicative of depression, than their matched population controls. Even with a seemingly good recovery (modified Rankin Scale score, 0) at 12 months after sIA-SAH, there is a significant risk of depression requiring antidepressant medication.